EXPLOITATION OF PRAWN RESOURCES BY TRAWLERS OFF KAKINADA WITH A NOTE ON THE STOCK ASSESSMENT OF COMMERCIALLY IMPORTANT SPECIES - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Annual prawn landings by trawlers operating from Kakinada increased gradually from 132 t in 1967to 6,191 t in 1977 and declined abruptly to 2,026 t in 1978. Effort in trawling hours also indicated moreor less a similar trend. The annual CPH indicated four phases in the abundance of prawns over the 12-year period. The annual percentage composition of prawns in the trawler catches varied from 16.7 in1968 to 30.2 in 1972 with the average at 25 %. Although 38 species of penaeids and a number of nonpenaeidswere represented in the catches, only Metapenaeus dobsoni (28.3%), M.monoceros (11.9%), M.brevicornis (6.6 %), M. affinis (5.9 %), Penaeus indicus (4.8 %) and P. monodon (4.4 %) formed the mainstayof the fishery. However, during 1977 non-penaeids represented by Acetes erythraeus, Nematopalaemontenuipes and Hippolysmata ensirostris formed about 55 % of the prawn catches relegating the penaeids toa secondary status. Length-frequency distribution of penaeid species indicated that there was a declinein the proportion of larger size groups in the latter years. MSY and FMSY have been calculated fordifferent species of penaeids to assess the present status of the stocks of these species. For the penaeidsas a group the MSY has been estimated at 2,589 t. The study indicates that almost all the penaeid speciesare being harvested at the optimum level and any further increase in effort may lead to overfishing ofthe stocks.